Association of the Cumulative Dose of Radioactive Iodine Therapy With Overall Survival in Patients With Differentiated Thyroid Cancer and Pulmonary Metastases - Yang, Jing (Front Oncol, 2019)
Purpose: The optimal cumulative dose of radioactive iodine therapy (RAIT) for patients with differentiated thyroid cancer (DTC) and pulmonary metastases (PM) is not known, therefore we evaluated the association between the cumulative dose of RAIT and overall survival (OS). Methods: A total of 202 patients with DTC and PM who underwent thyroidectomy and RAIT were analyzed in this study. The median cumulative dose of RAIT was 530 mCi. OS was compared with an age- and sex-matched general population from China to assess relative survival. Multivariable proportional hazards model smoothing by penalized spline was applied to identify independent predictors and examine the adjusted non-linear association of cumulative dose of RAIT and patient age with mortality. Results: The observed survival and relative survival at 10 years was 54.96 and 60.81%, respectively, with the standardized mortality ratio being 5.34. The cumulative dose of RAIT was associated with mortality in a dose-dependent fashion without an apparent cutoff point after adjustment of other variables. A linear but moderate association was found in the dose of 300 to 1,000 mCi. Cumulative dose of RAIT, patient age, diameter of pulmonary metastases, and extrapulmonary metastases were identified as independent predictors for OS. The increasing patient age was associated with mortality in a non-linear pattern, with the optimal threshold being 40 years. With advancing age, the risk of death increases rapidly in patients aged 40 years and younger, but slowly in patients over 40 years. Conclusions: RAIT should be assigned to RAI-avid patients until disease has been controlled or RAIT becomes refractory after consideration of the potential long-term side-effects. Patient age was associated with OS in a non-linear pattern, with a threshold at 40 years. Consideration of age as a binary variable could elucidate a more accurate prognosis in such patients.